Diseño de un plan de marketing para la empresa Durypconstruc Cía. Ltda. Dedicada a la construcción de estructuras metálicas ubicada en la cuidad de Quito en el Sector El Batán - Armijos Torres, María Alexandra (2013)
In summary, the first step will be the identification of the theoretical sources that will support the proposal, appointment is the main reference and theoretical basis for technical development of the proposal will be discussed later general business aspects DURYPCONSTRUC CIA LTDA., and will gather information about the management of the determining factors such as customers, competitors, etc.., Is done well in gathering information through surveys of potential customers, which will identify the needs of customers and existing demand at present the type of product offered by the company, will also develop the Department's proposal and marketing plan for the company, which is the fundamental tool of technical support to the operations of the department, and finally will be the development of financial study, which will determine the viability of the project, and this will serve as a tool for decision-making in the company on the proposal to improve the same.